Physics motivation and detector upgrades for the new era of the ATLAS experiment - Jason Nielsen (SciPost Physics Proceedings, 2022)
The ATLAS experiment at CERN’s Large Hadron Collider (LHC) will be upgraded in two stages to prepare first for the Run 3 data-taking campaign, during which the integrated luminosity will roughly double, and then for the High-Luminosity LHC program with an ultimate integrated luminosity of up to 4 ab-1. These upgrades and high-statistics datasets will allow ATLAS to perform searches and precision measurements to constrain the Standard Model in yet-unexplored phase spaces and in the Higgs sector. This contribution summarizes the ATLAS detector upgrades and selected physics prospects for Run 3 and the HL-LHC.